Canadian Federalism and Constitutional-Legal Status of Quebec Paradiplomacy - Yury Germanovich Akimov (Управленческое консультирование)
The article deals with legal and constitutional background of the paradiplomacy of Quebec, only French-speaking Canadian province. It reveals the specificity of division of competences between the center and the provinces, and shows features of the constitutional regulation of foreign policy in Canada. The article analyzes the cases that have affected federal-provincial relations in the field of implementation of international treaties negotiated by the Canadian federal government. Special attention is given to the Gérin-Lajoie doctrine of provincial internal competence extension formulated in 1965 on the basis of these cases. It also identifies the main trends of federal-provincial relations concerning the legal regulation of the international activity of Canadian provinces in the last third of XX - beginning of XXI c. It concludes the importance of federal-provincial cooperation in the respective sphere.